The influence of hydro‐climatic and anthropogenic effects on the long‐term variation of commercial fisheries in a large floodplain river - Rabuffetti, Ana Pia (2020)
This study deals with the effects of climate fluctuations and anthropogenic impacts on fisheries of Paraná River over the last 100 years. It is the first attempt to appraise the influence of hydro-climatic and anthropogenic variables on the population changes of the most important inland fisheries of Argentina. Datasets covering more than eight decades (1935–2016) of a number of frequent and abundant commercial species inhabiting the main channel as well as the large floodplain of Paraná River were used. Our results suggest that fish catches and structure changed over time. Long and short-term changes and reductions were closely related to fluctuations of 18 hydro-climatic variables. Positive effects on the ichthyofauna were recorded during humid periods (1930–1940 and 1970–2000), when the frequency of large spring–summer floods increased. An increase in anthropic impacts (accounted for with nine variables) were recorded during the last two decades. We highlight the usefulness of the approach to support the management of the resources, ensuring sustainability of commercial fish assemblages and the long-term conservation of biodiversity in big rivers.